Resistance and assimilation through folklore revival in selected works of Native American poets - Saddam, Widad Allawi (2017)
The coming of Europeans to the continent of America in the fifteenth century has brought in vast changes to the lives of Native Americans. It also led to centuries of conflicts and adjustment between the old and the New World. Although the Native Americans were rich with culture and tradition, they often were seen as barbaric by the colonizers. This study intends to show that the Native American Folklore in their poetry has remained a strong force that kept them connected to their ancestral heritage. The study uses Frantz Fanon’s views to first illustrate the process of assimilation in general between the Natives. Then, it progresses to analyse each poem in the light of the post colonial theory in order to highlight how the selected poets gave evidence to the ongoing assimilation in their poetry. The final step further uses Fanon’s theory to talk about the resistance and anti- assimilation poetry of the chosen writers. A lot of studies have been conducted on Native American Literature but very little dealt with folklore particularly in tackling poetry by poets like Simon Ortiz, Joy Harjo and Luci Tapahonso. These poets grew in immigrant families in America which represents a challenge to them since they face the dilemma of abandoning their cultural identity through assimilation into the mainstream Anglo-American culture and they are often known for promoting assimilation between the Native Americans and white people. However, this present study argues that the poetry written by these chosen writers has other hidden motives seen in the light of post colonial theory through the concepts of resistance, assimilation, and hybridity. It will scrutinise how the mentioned folklore has been passed down from generation to generation through storytelling and daily education of the young by the elders. It will also investigate how the poets subtly show their resistance to assimilation of the Western culture, and how they used poetry as a tool for revival of their culture.